Accounting as a choice of academic program / Maheran Zakaria , Wan Noor Asmuni Wan Fauzi and Siti Jeslyn Hasan - Zakaria, Maheran; Wan Fauzi, Wan Noor Asmuni; Hasan, Siti Jeslyn (University Publication Centre (UPENA), 2012)
The objective of this study is to examine the factors that influence students to choose accounting as their academic program. Utilising the Theory of Reasoned Action, the study predicted that students' intention to choose accounting as their academic program is influenced by their attitude towards accounting subject and subjective norm. Data were collected via survey of which approximately 400 sets questionnaire were sent to accounting students of Universiti Teknologi MARA Kelantan. From this amount, 340 students responded with the response rate of 85.0 percent. The results were analyzed using SPSS 17 and from the findings, it can be concluded that both attitude towards accounting program and subjective norms are positively related in influencing students' decision to choose accounting as an academic program. The findings provide useful insights for policy makers, accounting professional bodies and higher learning institutions in formulating strategies to promote the accounting program to tertiary students.